Air quality impacts of electric vehicle adoption in California. (1st February 2023) - Skipper, T. Nash; Lawal, Abiola S.; Hu, Yongtao; Russell, Armistead G.
Abstract: The transition of onroad vehicles from internal combustion engine vehicles to electric vehicles (EVs) has been promoted in the United States at federal and state levels to reduce emissions of conventional air pollutants and CO2 . One state level effort is a plan from California to mandate that all new passenger vehicle sales are EVs by 2035. Using the Community Multiscale Air Quality (CMAQ) model, we analyze the potential air quality impacts of having varying amounts of EVs in the California fleet for a historical (2016) and a future (2028) year, with emphasis on ozone (O3 ) and fine particulate matter (PM2.5 ). We find that for both PM2.5 and O3, reductions in concentrations scale approximately linearly with increasing EV fleet turnover. Improvements in air quality are widespread throughout the state, with the largest improvements occurring near Los Angeles and throughout the Central Valley. With full electrification of onroad vehicle fleets, the statewide population-weighted annual average PM2.5 concentration is reduced by about 0.5 μg/m 3 for both 2016 and 2028. Reductions in state population-weighted average fourth highest MDA8 O3 are 6.6 ppb and 4.3 ppb for 2016 and 2028. The results indicate that there are air quality benefits, and thus health benefits, to be gained from the transition to EVs and that these benefits do not diminish with increasing rates of EV adoption. Graphical abstract: Image 1 Highlights: Vehicle electrification results in significant reductions in PM2.5 and ozone. Air quality improvements are largest in Los Angeles and the Central Valley. Reductions in PM2.5 and ozone scale approximately linearly with electrification. Reductions in population weighted average PM2.5 exceed unweighted average. Brake wear, tire wear, and road dust are still significant sources of emissions.